"You're in That Realm of Unpredictability": Mateship, Loyalty, and Men Challenging Men Who Use Domestic Violence Against Women. (August 2014) - Towns, Alison J.; Terry, Gareth
This study reports on discourse analysis of transcripts from focus group discussions held with 28 "ordinary" men about domestic violence. Two broad "mateship" themes emerged: (a) a strong "mateship" discourse that produced public/private boundaries around discussions about intimate heterosexual relationships. Policed by the threat of violence, these boundaries prevented some men from challenging men about their violence. (b) "Loyalty to mates" discourses constituted attention to men's violence against women as threatening the moral integrity of all men. Finally, some men positioned themselves against men's domestic violence, distinguishing their masculinity from men who abuse women. Implications for prevention campaigns are discussed.